Performance study on a floating wind turbine - Lim, Pin Hong. (2013)
The effects of wave motions on the performance of an offshore floating wind turbine were studied by conducting experiments in a controlled environment inside a wind tunnel. Wave forces applied on the wind turbine structure can induce motions of multiple degrees of motion. By separating the motions to individual degree of freedom, a better understanding of how each motion affects the performance of the wind turbine can be achieved. In this study, the heave motion was chosen. To mimic the heave motion of a wave, a linear actuator was used. To create a wave model closest to an actual sine wave, a segmented sine wave model was adopted. With the help of the Froude scaling law, proper comparisons between the model and the actual full-scale structure could be made. The experiment used triangle waves to study heave motion without a wave pattern, segmented sine wave to study how it differs from triangle waves and finally segmented waves following the Froude scaling to study the effects when translated to a real full-scale structure. The study concluded that the heave- motion effects are insignificant when converted to real full-scale, which however may be subjected to inaccuracy in measurements due to the equipment used. A study with the combination of all degrees of freedom is worth looking into in the future.